CONSERVATIVE TREATMENT OF PELVIC BONE FRACTURES IN PATIENTS OVER 65 YEARS OLD - Solod, E. I.; Alhajj, A.; Abdulkhabirov, M. A.; Papoyan, V. S.; Bekshokov, K. K. (Bulletin of Pirogov National Medical & Surgical Center, 2025)
Due to the general increase in life expectancy of the population, the number of elderly and senile people suffering from osteoporosis is increasing in the world. Pelvic bone fractures that occur against the background of osteoporotic changes in the bones of the skeleton are distinguished by a number of characteristic features and are associated with a high mortality rate. If in the young population the main cause of these fractures are high-energy injuries resulting from road accidents and falls from a great height, then in elderly patients with concomitant osteoporosis, pelvic fractures can occur as a result of a fall from their own height. Fragility of bone tissue, the presence of a large number of chronic diseases and impaired adaptive capacity of the body in elderly patients complicates surgical fixation of pelvic ring fractures using various metal structures, which forces clinicians to adhere to conservative treatment tactics. Aims: to study the medium-term and long-term results of conservative treatment of pelvic bone injuries in patients over 65 years of age. Materials and methods . During the period from 2021 to 2024, a total of 30 patients (mean age 72±6.21 years) over 65 years old with pelvic bone fractures were treated at the A.K. Yeramishantsev City Clinical Hospital. The distribution of pelvic bone fractures according to the AO/OTA classification was as follows: type A in 6 (20%) patients, type B in 18 (60%), acetabular fracture in 6 (20%) patients. Results and conclusions. The mid-term treatment results after 6 months were assessed in 30 (100%) patients (in 6 they were excellent, in 16 – good, in 6 – satisfactory, in 2 – poor). The remote treatment results after 12 months were assessed in 24 (80%) patients (in 6 of them they were excellent, in 12 – good, in 4 – satisfactory, in 2 – poor). After 2 years, 16 (53%) patients were assessed (4 had excellent results, 8 had good results, 2 had satisfactory results, and 2 had poor results). 26 (86%) patients restored their previous activity level. Mortality was 0%. The analysis of pelvic fracture treatment results showed that in elderly patients with a comorbid history, it is preferable to adhere to conservative treatment tactics.